Analisis financial distress pada perusahaan telekomunikasi yang terdaftar di Bursa Efek Indonesia periode 2016-2021 - Matahari, Matahari; Akbar, Abdi; Anwar, Anwar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the Financial Distress of Telecommunication Companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The data collection technique used is the documentation method. The analytical technique used to measure, identify, and describe the possibility of financial distress. The results of the study show that there are telecommunications companies for the 2016-2021 period that are in a healthy condition (safe zone), namely PT. Telkom Indonesia Tbk, 2016-2019. The companies that are in the gray area are PT. Telkom Indonesia Tbk in 2020-2021. And there are companies that are in a state of bankruptcy (distress zone) including PT. Bakrie Telecom Tbk, PT. XL Axiata Tbk, PT. Smartfren Telecom Tbk, PT. Indosat Tbk.